Metode Pembelajaran Seni Budaya dan Prakarya dalam Menumbuhkan Kreativitas Seni Peserta Didik MI Salafiyah Kajen - Lestari, Putri Yuli; Kinesti, Rakanita Dyah Ayu (Lembaga Yasin AlSys, 2025)
Arts education plays a vital role in shaping individuals who are creative, possess aesthetic sensitivity, and demonstrate social and cultural awareness. This study aims to explore how teaching methods in Cultural Arts and Crafts (Seni Budaya dan Prakarya, SBDP) foster students’ artistic creativity at MI Salafiyah Kajen. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The findings reveal that teachers utilize three main methods in SBDP instruction: lecture, demonstration, and project creation. The lecture method conveys fundamental concepts, demonstration illustrates artistic techniques, and the project creation method encourages students to produce projects that sharpen skills and stimulate creativity. This combination of methods proved effective in nurturing students’ artistic creativity across ideas, techniques, and final works. The study concludes that a contextual and student-centered teaching strategy can optimally develop artistic potential. The implication is that teachers should continuously refine learning approaches that encourage creative exploration to support the formation of aesthetic and innovative character traits in students.